COVID-19 outbreak in vaccinated patients from a haemodialysis unit: antibody titres as a marker of protection from infection. Issue 7 (1st February 2022) - Boudhabhay, Idris; Serris, Alexandra; Servais, Aude; Planas, Delphine; Hummel, Aurélie; Guery, Bruno; Parize, Perrine; Aguilar, Claire; Dao, Myriam; Rouzaud, Claire; Ferriere, Elsa; Knebelmann, Bertrand; et al.
ABSTRACT: Background: Patients on maintenance haemodialysis (HD) have an increased risk of severe coronavirus disease 2019 (COVID-19) and a reduced response to vaccines. Data are needed to identify immune correlates of protection in this population. Methods: Following a COVID-19 outbreak among vaccinated patients in a HD unit, clinical data and serological response to BNT162b2 vaccine were retrospectively recorded. Results: Among 53 patients present in the dialysis room, 14 were infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) alpha variant (COVID_Pos) and 39 were not. Compared with uninfected patients, COVID_Pos patients more frequently had additional causes of immunosuppression (50% versus 21%; P  = .046) and were more often scheduled on the Monday–Wednesday–Friday (MWF) shift (86% versus 39%; P  = .002). Moreover, COVID_Pos had lower anti-spike (S) immunoglobulin G (IgG) titres than uninfected patients {median 24 BAU/mL [interquartile range (IQR) 3–1163] versus 435 [99–2555]; P  = .001} and lower neutralization titres [median 108 (IQR 17–224) versus 2483 (481–43 908); P  = .007]. Anti-S and neutralization antibody titres are correlated ( r  = 0.92, P  < .001). In multivariable analysis, an MWF schedule {odds ratio [OR] 10.74 [95% confidence interval (CI) 1.9–93.5], P  = .014} and anti-S IgG titres 1 month before the outbreak [<205 BAU/mL: OR 0.046 (95% CI 0.002–0.29), P  = .006] were independently associated with COVID-19 infection. None of the patients with anti-S IgG >284 BAU/mL got infected. Ten of 14 COVID_Pos patients were treated with casirivimab and imdevimab. No patient developed severe disease. Conclusions: Anti-S IgG titre measured prior to exposure correlates to protection from SARS-CoV-2 infection in HD patients. BNT162b2 vaccination alone or in combination with monoclonal antibodies prevented severe COVID-19.